Kebijakan Dividen sebagai Moderasi Pengaruh ROA, PER, dan PBV Terhadap Return Saham pada Perusahaan Sektor Infrastruktur Sebelum dan Sesudah Pandemi COVID-19 - Muhammmad Iqbal Yuliansyah; Gatot Nazir Ahmad; Titis Fatarina Mahfirah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study analyzes the effect of Return on Assets (ROA), Price to Earning Ratio (PER), and Price to Book Value (PBV) on stock returns, with Dividend Payout Ratio (DPR) as a moderating variable in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during 2017–2022. The research aims to understand the factors influencing stock returns and the role of external factors, such as the COVID-19 pandemic, in these relationships.Using secondary data from financial reports of 54 companies with a total of 295 observations, the study employs unbalanced panel data regression analyzed using STATA. The results show that ROA and PER do not significantly affect stock returns. PBV significantly influences stock returns during the combined period (2017–2022) but not in separate periods before and during the pandemic. DPR significantly affects stock returns but does not moderate the relationships between ROA and PER with stock returns. Interestingly, DPR strengthens the relationship between PBV and stock returns only before the COVID-19 pandemic. These findings indicate that PBV and DPR can influence stock returns, although their impact varies across economic periods. This study provides important insights for designing adaptive investment strategies and dividend policies based on market conditions.